Legitimizing Factors of the American Hegemony: The Changing Role of Coalitions and Partnerships - A. N. Bogdanov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2022)
Since the end of the Cold War the United States sought to enhance its privileged position as a ‘leader’ of the international community, capable of mobilizing and coordinating other states to achieve collective goals and ensure shared values. For this purpose, the U.S. relied on traditional alliances and intergovernmental organizations as mediators in relations between Washington and the less powerful countries in order to ensure the legitimacy of the American engagement. However, one can witness the United States’ reorientation towards more flexible and less institutionalized formats of interaction in recent years. It may be considered as the transformation of power relations underlying ‘liberal international order’. Although the established U.S.-led alliances still serve as the pillars of the ‘American hegemony’, many functions are increasingly carried out beyond the frameworks of the alliances, and the less institutionalized structures are becoming increasingly important. Thus, it is necessary to explore the links between legitimacy concerns and evolution of institutional tools, whereby the international order congenial with the U.S.’ interests can be maintained. The paper examines the views of both Russian and Western expert communities on the role of U.S. coalitions and partnerships in ensuring legitimacy of the postCold War ‘American hegemony’. The author notes that the existing approaches pay insufficient attention to the dynamics of power relations between the United States and its partners and allies. To fill this gap, the author engages theoretical assumptions of the English school, which consider the issue of ‘legitimacy’ within the framework of the concept of ‘international society’ — the group of states within which the division of roles and social stratification are intertwined with the processes of reproduction and transformation of power relations. On this basis the author explores the specifics of the United States’ partnerships and ad hoc coalitions as the tools of legitimizing the ‘American hegemony’ after the end of the Cold War. The author concludes that the use of these mechanisms allows the United States to effectively mobilize collective efforts and manage the distribution of roles between its allies and partners. However, it generates additional risks and challenges in times of tensions.